Menggugat Khilafah Islamiyah: Sejarah Politik Islam dalam Pembacaan Farag Fouda - Musthafa, Adib Khairil (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2025)
Abstract: Farag Fouda, a prominent Muslim intellectual who tragically fell victim to the brutality of Islamist fundamentalist groups in Egypt, was one of the key figures who sought to critically examine Islamic history. His exploration and reinterpretation of Islamic political history ultimately made him a target of violent fundamentalist groups in the country. Fouda’s thoughts on the relationship between religion and the state called for a thorough historical inquiry and a new interpretive framework for understanding Islamic political history. This article employs a qualitative-descriptive approach based on library research to analyze Fouda’s critical reflections on the political history of Islam. It aims to present Farag Fouda’s historical perspectives, particularly his critiques of Islamic political history. The article is structured around three main themes: Fouda’s critique of political Islam, his reading of Islamic political history, and his analysis of the historical trajectory from the era of the Khulafa al-Rashidun to the Abbasid period. These thematic categories are formulated based on the assumption that Fouda’s views on the religion-state relationship fundamentally underpin his interpretation of Islamic history. Through his writings, Fouda offers a sharp critique, systematically exposing the weaknesses in the ideological foundations of the Khilafah Islamiyah. Abstrak: Farag Fouda, tokoh pemikir muslim yang menjadi korban tragis kelompok fundamentalis Islam di Mesir, adalah salah satu tokoh yang berusaha membaca dengan kritis sejarah Islam. Namun, sebab penelusuran dan interpretasinya atas sejarah politik Islam menyebabkan dirinya menjadi sasaran kebrutalan kelompok fundamentalis Islam di Mesir. Pemikiran Farag Fouda tentang hubungan agama dan negara, menghendaki kerja penelusuran sejarahnya pada interpretasi baru atas sejarah politik Islam. Artikel ini menggunakan pendekatan kualitatif-deskriptif berbasis studi pustaka (library research) untuk memahami pikiran dan pembacaan kritis Fouda atas sejarah politik Islam. Artikel ini akan menyajikan pemikiran historis Farag Fouda atas sejarah Islam, terutama mengenai Sejarah politik Islam. Ketegori pembahasan dalam artikel ini adalah mengenai; Kritik Farag Fouda tentang Islam Politik; Pembacaannya atas sejarah Islam Politik; dari masa khulafa’aurrasyidun hingga masa Abbasiyah. Kategori pembahasan tersebut dirumuskan berdasarkan asumsi bahwa pemikiran Farag Fouda mengenai hubungan agama dan negara, sesungguhnya ikut serta melandasi interpretasinya terhadap sejarah Islam.  Fouda menyajikan kritik dalam pembacaannya, ia menguraikan dengan baik kelemahan-kelemahan argumen khilafah Islamiyah.